2012
DOI: 10.1186/1742-2094-9-96
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of microglial cathepsin C expression and activity in lipopolysaccharide-induced neuroinflammation

Abstract: BackgroundCathepsin C (Cat C) functions as a central coordinator for activation of many serine proteases in inflammatory cells. It has been recognized that Cat C is responsible for neutrophil recruitment and production of chemokines and cytokines in many inflammatory diseases. However, Cat C expression and its functional role in the brain under normal conditions or in neuroinflammatory processes remain unclear. Our previous study showed that Cat C promoted the progress of brain demyelination in cuprizone-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 69 publications
4
59
0
Order By: Relevance
“…In our previous study, the up-regulated expression of Cat C was mainly found in microglia/macrophage lineage cells in LPS–induced neuroinflammation (Fan et al, 2012). To further confirm the cellular source of Cat C, we performed c-fms ISH and Iba-1 IHC staining, which are commonly used as a marker of microglia/macrophages, to detect microglia/macrophages in wild and Cys F KO mice after cuprizone treatment.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In our previous study, the up-regulated expression of Cat C was mainly found in microglia/macrophage lineage cells in LPS–induced neuroinflammation (Fan et al, 2012). To further confirm the cellular source of Cat C, we performed c-fms ISH and Iba-1 IHC staining, which are commonly used as a marker of microglia/macrophages, to detect microglia/macrophages in wild and Cys F KO mice after cuprizone treatment.…”
Section: Resultsmentioning
confidence: 87%
“…Cat C can activate serine proteases in T cells, natural killer cells, neutrophils, and mast cells (Hamilton et al, 2008). Also, we previously found Cat C is predominantly expressed in hippocampal CA2 neurons in normal mice, but up-regulated in activated microglia in neuroinflammation induced by LPS intraperitoneal injection (Fan et al, 2012). Taken together, we believed that knockout of Cys F aggravated cuprizone-induced demyelination might be related to Cat C expression.…”
Section: Resultsmentioning
confidence: 89%
“…However, the lack of evidence for TLR4 expression in ARC neurons in addition to the scarcity of conclusive studies on the direct effects of the endotoxin over hypothalamic neurons, precludes meaningful assumptions that LPS would directly act on neuronal populations to inhibit feeding. Microglial cells, known for a long time as central sentinels of brain injury, express TLR4 and produce cytokines under LPS stimulation [Milanski et al, 2009; Saijo and Glass, 2011; Borges et al, 2012; Fan et al, 2012]. These findings support the idea of microglia acting to inhibit food intake under endotoxin challenges.…”
Section: - Hypothalamic Control Of Food Intake During Inflammationmentioning
confidence: 55%
“…In addition to MMPs, increased activity of other proteases such as cathepsins has been observed in ulcerating corneas secondary to xerophthalmia 37 or severe burns, 38 indicating that these molecules may also play a role in corneal destruction. IL-1b up-regulates cathepsin expression in microglial cells 39 as well as in gastric epithelial cells and macrophages. 40 Tranilast was found to attenuate inflammation associated with collagen-induced arthritis in mice by inhibiting the expression of inflammatory cytokines as well as that of cathepsins and other proteases.…”
Section: Discussionmentioning
confidence: 99%